Preference of Educational Philosophy and Philosophical Mindedness of Iranian Physical Education and Sport Science Lecturers - Fatemeh Ghorbanalizadeh Ghaziani; Seyed Mohammad Hosein Razavi; Siavash Khodaparast Sareshkeh; Rohollah Ghasemi (The Society of Aging and Physical Activity (SAPA), 2014)
The aim of this study was to investigate educational philosophy and philosophical mindedness of Iranian physical education and sports science lecturers (state-run Universities and Islamic Azad Universities). 150 questionnaires were randomly distributed among them, 123 filled questionnaires returned and finally 98 were confirmed. Two major instruments of Philosophy Preference Assessment (PPA) constructed by Wiles and Bondi (2010) with Cronbach's alpha = 0.859, and Philosophical Mindedness (PM) constructed by Soltani (1996) with Cronbach's alpha = 0.86 based on Smith model were used to examine the research hypotheses. The results showed that experimentalism and realism were the first and second educational philosophy of Iranian physical education lecturers, respectively (p = 0.001). Also, comprehensiveness, penetration, and flexibility are the first, second, and third philosophical mindedness preference, respectively (p = 0.001). It is difficult for many people to build their beliefs based on a philosophical thought and special philosophical principles; therefore eclecticism is the combination of concepts from philosophical aspects in form of a harmonic belief. Thoughtful combination of beliefs builds a mature philosophical viewpoint. Also, it seems that it is necessary for lecturers to have comprehensiveness, penetration, and flexibility equally and consonantly, so we can say that they were equipped with philosophical mindedness.